IDENTIFICATION OF MACROFAUNAATTACHED ASSOCIATED WITH MANGROVE IN SUNGAITOHOR VILLAGE MERANTI DISTRICT RIAU - Fitriansah, Heru; Samiaji, Joko; Nurrachmi, Irvina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Literatures on macrofauna organisms attached to mangrove islimited. The purpose of this research is to obtain the informationon macrofauna organism within the mangrove ecosystem. The research was conducted in December 2017. method used was direct purposive sampling. Macrofauna organisms attached and mangrove type were identified using identification books. The results obtained indicate that the most dominant organisms belonged to molluscs and crustaceans. Seven gastropod species and two crustaeans were(Cerithideacingulata, Cerithideaquadrata, Neritalineate, Chicoreuscapucinus, Cassidulaaurisfelis, Achatinellamustelina, Echinolittorinavidua, BalanusspandLlyoplaxsp). The type of mangrove vegetations were consistedof found, (Avicennia alba, Rhizopora apiculata,). Keywords:macrofauna, mangrove ecosystem, sungaitohor